Penghindaran Pajak: Dampak Profitabilitas, Leverage dan Pertumbuhan Penjualan - Fitria, Giawan Nur; Bintara, Rista (Media Akuntansi Perpajakan, 2022)
The purpose of this study was to determine the effect of profitability, leverage and sales growth on tax evasion. This research is a causal research using the multiple regression analysis method with the help of the SPSS test tool version 25. The object of this research is a coal mining company listed on the Indonesia Stock Exchange from 2016 to 2020. The sample used was 90 data according to the criteria in sample selection using purposive sampling technique. The results of the data analysis show that profitability has an effect on tax evasion, while leverage and sales growth have no significant impact on tax evasion. Profitability has a significant impact on tax avoidance by companies, for this reason companies are expected to pay attention to the level of profitability because profitability is an investor's assessment of company performance. Regarding the leverage policy and the amount of sales growth, it cannot be proven that it has an impact on tax evasion, therefore companies can use non-debt tax shields as an effort to consider planning smaller tax payments. In this case the company's fixed asset depreciation expense can reduce the amount of tax paid by the company.